Jenis-Jenis Hak Jaminan Dalam Perspektif Hukum Perdata dan Hukum Islam : Studi Konseptual - F, Fauzan; Diana, Nailah Nur; Amelia, Rizki; Latif, A. (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This journal aims to analyze the various types of collateral rights regulated in civil law and Islamic law, by highlighting the differences and similarities in the underlying principles. From a civil law perspective, collateral rights function as a means of protection for creditors in order to obtain debt payments from debtors. These types of collateral rights include mortgages, pawns, and fiduciaries, each of which has different characteristics and implementation procedures. Meanwhile, in Islamic law, the concept of collateral rights is regulated based on sharia principles that prioritize justice and avoid usury. Types of collateral in Islamic law such as rahn (pawn) and hawalah (transfer of obligations) have different characteristics compared to civil law. The research method used is a qualitative approach. Data were collected through a literature review, which includes books, articles, and relevant laws and regulations, and analyzed by comparing civil law provisions with Islamic law principles related to collateral rights.